キホウ ヲ フクム ヒョウショウ コオリ ノ アツミツ カンワ カテイ ノ リロン テキ ケンキュウ - Salamatin, Andrey N.; Lipenkov, Vladimir Ya. (1993)
P(論文) この解説は, 筆者らがロシアにおいて1983年から1989年にかけて行った一連の研究のレビューである。均一な気泡を含む氷の圧密(あるいは膨張)過程の理論的検討を行う。極地氷床における密度の深度プロファイルおよび掘削後の体積膨張をシミュレーションするための数学的モデルを展開し, それを東南極ボストークにおける掘削コアに適用する。また, 気泡から空気水和物結晶への遷移に対する簡単なモデルを提案する。 This paper presents a brief review of the authors' earlier research on polar ice density modeling carried out and published (in the main) during 1983-1989 in Russia. A theoretical approach to macrocontinuum description of bubbly ice densification (expansion) on the basis of averaging asymptotic methods is considered. Mathematical models for the simulation of polar ice sheet density variations versus depth and for the prediction of deep ice core volume relaxation after its recovery are developed and tested on real situations at Vostok Station, East Antarctica. A simplified model of the equilibrium transformation of bubbles entrapped in ice into air hydrate crystals is proposed. departmental bulletin paper